P101 ARRHYTHMIC MITRAL VALVE PROLAPSE: COULD ELECTROANATOMICAL MAPPING AND CARDIAC MAGNETIC RESONANCE BE GOOD FRIENDS?. (18th May 2022) - Piscitelli, L; Pedone, C; Perugini, E; Coutsoumbas, G; Riva, L; Dattolo, G; Carinci, V; Barbato, G; Cardelli, L; Casella, G
Abstract: Background: There is an increasing awareness of the association between mitral valve prolapse (MVP) and sudden cardiac death (SCD), but risk stratification is still challenging. Mitral annular disjunction (MAD) is a recognized risk factor for arrhythmic complications. A multimodality imaging strategy, including advanced echocardiography, magnetic resonance (CMR) and electromechanical mapping, could improve risk stratification and management by combining anatomical and functional information. Case Review: We report a case of a 50–year–old woman without cardiovascular risk factors, complaining for worsening palpitations in the last months. Echocardiogram documented bileaflet MVP with moderate regurgitation, MAD (12 mm in inferolateral wall) and normal ventricular systolic function. 24–hour Holter monitoring revealed a high (13%) premature ventricular complexes burden with ventricular bigeminy and non–sustained ventricular tachycardia. Stress test showed a reduction of the arrhythmias during exercise. CMR confirmed MAD but no late gadolinium enhancement areas were detected. The patient underwent electrophysiological study with electroanatomic mapping (CARTO). The latter revealed multifocal fragmented and delayed low voltage potentials close to the posterior papillary muscle and the posterior anular mitral area, respectively. Both locations were the targets of endoventricular radiofrequency ablation. However, due to her high arrhythmic risk profile the patient implanted a cardioverter defibrillator. Discussion: In arrhythmic risk stratification of MVP with MAD, CMR could have technical limitations due to diffuse fibrosis patterns or irregular cardiac rhythm that could undermine a detailed and complete evaluation. Thus, electroanatomical mapping during electrophysiological testing could offer additional and complementary information that could improve risk stratification and further management.